Borane‐Catalyzed Chemoselective and Enantioselective Reduction of 2‐Vinyl‐Substituted Pyridines - Tian, Jun‐Jie; Yang, Zhao‐Ying; Liang, Xin‐Shen; Liu, Ning; Hu, Chen‐Yu; Tu, Xian‐Shuang; Li, Xiang; Wang, Xiao‐Chen (Angewandte Chemie International Edition, 2020)
Herein, we report that highly chemoselective and enantioselective reduction of 2‐vinyl‐substituted pyridines has been achieved for the first time. The reaction, which uses chiral spiro‐bicyclic bisboranes as catalysts and HBpin and an acidic amide as reducing reagents, proceeds through a cascade process involving 1,4‐hydroboration followed by transfer hydrogenation of a dihydropyridine intermediate. The retained double bond in the reduction products permits their conversion to natural products and other useful heterocyclic compounds by simple transformations. A protocol for Lewis acid‐catalyzed highly chemoselective and enantioselective reduction of 2‐vinyl‐substituted pyridines has been developed. The reactions were catalyzed by chiral spiro‐bicyclic bisboranes and occurred under mild reaction conditions with high turnover numbers.